Interrelationship between vaginal mucus resistance, ovarian cycle and fertility in cows* - SHARMA, PRASHANT; TIWARI, R P; MISHRA, O P; SINGH, MOHAN (The Indian Journal of Animal Sciences, 2014)
Experiment using intravaginal probe with impedance meter were conducted to observe the pattern of vaginal mucus impedance during estrous cycle in normal cyclic s;ows (n=13) for prediction of estrus onset. Ultrasonography was performed to observe the development of corpus luteum/and follicle and their correlation with VMI. Vaginal mucus impedance in normal cyclic cows with external sign of estrus indicated lower VMI during onset of estrus (40.92Â±0.49 ohms). During metoestrus VMI value increased gradually to reach 60.92 Â± 1.06 ohms at the end of metoestrus. During dioestrus the VMI reached to highest value on day 12 of estrous cycle and then started decreasing. The size of largest ovarian follicle as monitored by ultrasonography had significant (P